Essential training variables of arm-hand training in people with cervical spinal cord injury: a systematic review - Nele Bertels; Henk Seelen; Justine Dembele; Annemie Spooren (Medical Journals Sweden, 2023)
Objective: To identify and evaluate 3 training variables of motor training programmes involving people with a cervical spinal cord injury: i.e. motor training strategies, therapy dosage, and persons' motivation for arm-hand functioning in subacute and chronic phases. Methods: PubMed, Cochrane, CINAHL, EMBASE, and DARE databases were searched for active arm-hand motor training programmes. Two independent reviewers assessed methodological quality. Pre-post effect sizes were calculated using Hedge's g, and mean effect sizes were calculated to compare outcomes on the International Classification of Functioning, Disability, and Health levels of function and activity. Results: Twelve training programmes integrated mainly skill training alone or combined with strength and/or endurance training. Task-oriented training components included: multiple movement planes, functional movements, clear functional goals, and bimanual practice. Training duration of 8 weeks was common. Quantitative analyses of 8 training programmes showed an overall small effect (0.34) on function level and an overall moderate effect (0.55) on activity level. In depth-analysis of activity level showed moderate effects of skill training only (0.55) or combined with strength and endurance training (0.53). Moderate effects (0.53-0.60) were found for integrating functional movements, clear functional goals, real-life object manipulation, multiple movement planes, total skill practice, context-specific environment, exercise variety, and bimanual practice. Training of minimum 8 weeks showed a moderate effect (0.60-0.69). Conclusion: Based on limited studies, arm-hand functioning aiming to improve activity level can be improved using skill training with at least 8 task-oriented training components, additional strength and endurance training, with a minimum training duration of 8 weeks.